Development of Interactive Animation Video Learning Media in Nahwu Learning for Grade 8 Muhammadiyah 1 Sidoarjo Middle School: Pengembangan Media Pembelajaran Video Animasi Interaktif dalam Pembelajaran Nahwu untuk Kelas 8 Sekolah Menegah Pertama Muhammadiyah 1 Sidoarjo - Shabrina, Almira; Hikmah, Khizanatul (Universitas Muhammadiyah Sidoarjo, 2023)
Learning media is an important aspect of supporting the achievement of learning objectives. However, currently learning Arabic in Class VIII SMP Muhammadiyah 1 Sidoarjo does not use learning media. Meanwhile, students have difficulty understanding Nahwu Adad Ma'dud learning and students need technology-based learning media that attracts interest in learning and is easy to use anywhere and anytime. So this research was carried out as a form of developing learning media, especially in learning Nahwu Adad Ma'dud which was aimed at eight grade of junior high school students to be more interested and motivated to learn Adad Ma'dud so that it was easier to understand. The research method used is Research & Development (R&D) by describing the responses from the questionnaire sheet as well as criticisms and suggestions from the validators, and the results of the responses are processed and measured quantitatively using the Linkert scale. This research is produce the development product of an interactive animation video with time duration 13 minutes that containing animated explain of the meaning, examples, and summaries of the 4 types of Adad Ma'dud. This interactive animation video development product reach a very good response by 86.16% from 15 students.